2021
DOI: 10.3389/fonc.2021.662806
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-Mesenchymal Transition in Colorectal Carcinoma: Comparison Between Primary Tumor, Lymph Node and Liver Metastases

Abstract: There is emerging evidence suggesting that epithelial-mesenchymal transition (EMT) and mesenchymal-epithelial transition (MET) play an important role in colorectal carcinoma (CRC), but their exact role remains controversial. Our aim was to analyze the miR-200 family as EMT markers and their target genes expression at invasive tumor front and in nodal and liver metastases. Sixty-three formalin-fixed paraffin-embedded tissue samples from 19 patients with CRC were included. Using a micropuncture technique, tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…In contrast, another study showed miR-200c upregulation in primary CRC compared to liver metastases [ 36 ]. However, to the best of our knowledge, this was the first report of miR-200c expression in lymph node metastases of CRC in comparison to primary CRC besides our previous study that focused on the epithelial-mesenchymal transition [ 37 ]. Furthermore, our results suggest that in contrast to a previous bioinformatics analysis [ 19 ], miR-200c has a positive influence on DCN expression in CRC metastases.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, another study showed miR-200c upregulation in primary CRC compared to liver metastases [ 36 ]. However, to the best of our knowledge, this was the first report of miR-200c expression in lymph node metastases of CRC in comparison to primary CRC besides our previous study that focused on the epithelial-mesenchymal transition [ 37 ]. Furthermore, our results suggest that in contrast to a previous bioinformatics analysis [ 19 ], miR-200c has a positive influence on DCN expression in CRC metastases.…”
Section: Discussionmentioning
confidence: 96%
“…Once the cancer cells exit the bloodstream and form micrometastases, a reverse process, called mesenchymal–epithelial transition, enables them to form metastatic lesions [ 45 ]. Tumor-associated macrophages (TAM), myeloid-derived stem cells (MDSC), and lymphocytes Th1/Tc infiltrating the TME influence the epithelial cells undergoing TME through the secretion of IL-1β, IL6, IL8, IL10, IL17, TGF-β, or TNFα [ 46 ].…”
Section: Cytokines Tumor Microenvironment and Epithelial–mesenchymal ...mentioning
confidence: 99%
“…Under the influence of IL-1β, IL-8, and TGFβ, which can affect Wnt/β-catenin signaling, cancer cells can gain stem-like qualities and form a subpopulation of cancer stem cells capable of self-renewal and recreation of the entire tumor population [ 47 ]. Simultaneously, the infiltration of suppressive immune cells into the TME increases, and the immunophenotype of local cells changes, leading to the failure of immune surveillance and cancer immune escape [ 36 , 39 , 45 , 47 ]. Hence, tumor-associated signaling is essential in understanding the pathogenesis of CRC and in applying potential therapeutic approaches.…”
Section: Cytokines Tumor Microenvironment and Epithelial–mesenchymal ...mentioning
confidence: 99%
“…A study on spindle cell carcinoma showed significant miR-141, -200a, -200c, and -429 downregulation in carcinoma tissue compared with normal mucosa [ 15 , 62 ]. Furthermore, downregulation of the miR-200 family showed a significant correlation with loss of E-cadherin, characteristic for EMT progression [ 15 , 63 , 64 , 65 ]. Another study demonstrated that restored levels of miR-200a inhibited tumor growth in vivo [ 66 ].…”
Section: Competing Endogenous Rna Networkmentioning
confidence: 99%